Description Analysis of Student's Scientific Literacy Skills in Biology Learning - Masru'ah, Masru'ah; Ni’mah, Zumrotun (Direktorat GTK Madrasah Ditjen Pendis Kementerian Agama Republik Indonesia, 2024)
In the 21st century, technology and information developments have spurred education to adapt and improve the system. Education is not only aimed at providing knowledge but also improving various skills in an effort to produce a smart and skilled young generation. Instilling and increasing students' scientific literacy skills is an action that can be done. Scientific literacy is the ability to fully and accurately understand science so that the students have sensitivity to themselves and their surroundings and can make decisions based on scientific considerations. The research purpose was to analyze students' scientific literacy in biology learning. This research is quantitative. Data collection using test and non-test methods. The data analysis shows that students' scientific literacy abilities are in the medium category. The results are expected to be an illustration for educators to be able to make improvements in the teaching and learning process.